Influence of annona muricata linn polymorphism on polyphenolic production and its anti cancer effects - Syed Najmuddin, Syed Umar Faruq (2016)
Often the conventional drugs had difficulties in combatting cancer mainly due to resistance to treatment and the risk of health setbacks, many has turned to medicinal plant for hope. Active constituents and compounds found in medicinal plant were proven effective in targeting cancer in vitro and in vivo levels while some of them had been subjected to clinical trial. While such findings on the medicinal plants are great and convincing, there is one aspect being overlooked and require as much attention.Given that a medicinal plant from certain place is rich with active compounds that serve the cancer therapeutic criteria, it is not necessarily to be the case for that similar plant found in another location i.e., level of its active compounds content might differ.In the present study, a total of 19 Annona muricata Linn (soursop) samples from different location (Peninsular Malaysia states: Johor, Melaka, Negeri Sembilan,Selangor, Perak, and Perlis) were evaluated on the basis of polymorphism influence on the polyphenolic level and cytotoxicity effect in targeting the breast cancer cells. The ISSR-PCR of the DNA samples indicated the presence of polymorphism (72.41%) among the Annona muricata Linn samples and was supported by the discrepancies of data results observed in antioxidant level and anti-proliferative assay of the leaf aqueous extract on breast cancer cells (MCF-7, MDA-MB-231, and 4T1). M1 AMCE had the highest content of phenolic (73.2 μg/mL GAE) and flavonoid (191.4 μg/mLCE) and also the highest antioxidant capacity in ORAC assay (254.7 μM) while A1 possessed the highest antioxidant capacity in FRAP assay. Based on the antiproliferative assay, B1 AMCE was the most potent in killing MCF-7 (IC50= 221.67 μg/mL) and 4T1 (IC50= 251.67 μg/mL) while J1 AMCE was the most potent in killing MDA-MB-231 (IC50= 347.67.67 μg/mL) cancer cells. Further downward assays were performed with the most potent leaf aqueous extract (B1 AMCE; dosage: 251.67 μg/mL) on 4T1 breast cancer cell line only to investigate its anti-cancer effect as it has a close resemblance of the advanced human breast cancer (stage IV); a cancer stage that patient has little chance of survival. B1 AMCE has a little effect (IC50= 1000 μg/mL) on the normal breast cell line, MCF-10A rendering its safe profile. The selected B1 AMCE managed to induce apoptosis in 4T1 cells as observed in the Annexin V/FITC and AO/PI assays as well as to arrest the cell cycle of 4T1 and induced the cells into sub G0/G1 stage.Metastasis of cancer cells is one of the hurdles needed to be curbed as it is the main factor leading to failure in cancer treatment. The anti-metastatic potential of B1 AMCE can be seen by the decreased percentage of migrated (31%) and invaded (44%) 4T1 cells in migration and invasion assays respectively. With the convincing results provided by the in vitro studies, the anticancer effects of B1 AMCE upon 4T1 breast cancer cells were further studied in vivo.The tumors harvested from 4T1 tumor-bearing mice showed a decrease in weight and volume from 1.45 g and 375 mm3 in the untreated group to 1.2 g and 271.7 mm3 in the B1 AMCE-treated group respectively. The H&E staining of sectioned tumor revealed a lower number of mitotic cells in the treatment group. B1 AMCE increased the circulation level of white blood cells and also regulated the immune system by increasing the population of helper and cytotoxic T-cells and natural killer cell population as well. The decreased level of angiogenesis-related protein and reduced number of metastasized 4T1 cell colonies to lung in the clonogenics assay exhibit the anti-metastatic potential of B1 AMCE on breast cancer and supported the in vitro studies. In addition, B1 AMCE treatment managed to reduce the oxidative stress caused by inflammation due to its antioxidant effect as evaluated by the nitric oxide and malondialdehyde assays. In conclusion, this study showed that the B1 AMCE is a promising candidate for cancer treatment especially in breast cancer and deserves further research as an alternative to conventional drugs while also stressed out the selection of Annona muricata sample which plays a significant role in determining its potential therapeutic effect on cancer.